PENGARUH BRAND IMAGE KARTU IM3 INDOSAT TERHADAP KEPUASAN LAYANAN DAN LOYALITAS PELANGGAN (Studi pada PTN dan PTKIN di Kota Malang) - Hutami, Virgistira Mulya; Rahayu, Yayuk Sri (IQTISHODUNA, 2016)
The study aims to determine the effect of brand image IM3 to loyalty, either directly or indirectlythrough the satisfaction. This research used a quantitative approach and the respondents which the customersof Indosat IM3 on four Universities in Malang . The data collection used accidental sampling method. Pathanalysis was used to test and analyze hypotheses by considering the classical assumption test. The resultsof the study showed that the brand image significantly affect the service satisfaction and customer loyalty.Indicators of Brand image contributed 47.5% to total customer satisfaction. Meanwhile satisfaction accountedfor 30.7% of customer loyalty. Two indicators of brand image consist of guarantees and social identificationhas no significant effect on customer satisfaction. While, two other indicators of brand image consist ofpersonal identification and status has a significant influence on customer satisfaction. From path analysisknown that there is indirectly influence of the status of personal identification to loyalty through customersatisfaction.